Efficiency of Land Reclamation Projects: New Approach to Assessment for Sustainable Soil Management - KUCHER, Anatolii; ANISIMOVA, Olha; HELDAK, Maria (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.10.7(39).14, 2020)
The purpose of the article is to highlight the results of the study on a comprehensive methodological approach to assessing the economic efficiency of land reclamation projects in the context of sustainable soil management in the agricultural sector. The theoretical bases of determination of economic efficiency of land reclamation investment-innovation projects are generalized. The scientific and methodical principles of determination of economic efficiency of soil reclamation and reclamation investment-innovation projects are formed. The scientific and applied approaches to the determination of economic efficiency were worked out on the example of a concrete reclamation investment and innovation project, which made it possible for a first time to carry out a comprehensive assessment of the economic efficiency of the project of reclamation plowing of solonetz chestnut under non-irrigated conditions, from the point of view of systemic, situational and interdisciplinary approaches. A macroeconomic assessment of the economic efficiency of a land reclamation project in Ukraine was carried out.